INVESTMENT AND DEVELOPMENT IN THE KURDISTAN REGION - Dliva Abdullah Ali , Dr. Ebad Rouhi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In order to achieve the development of growth, prosperity, and raising the level of national income, it has opened its doors to the arrival of Arab and foreign companies and investors to implement development projects and contribute to the economic process in the region. The research problem lies in studying the investment about itself, as the basic information is generally considered confidential between the investor and the country with which it was agreed. From the knowledge of the agreement, during which this information can be viewed in general, it gives us information about the mistakes that can be made by the investor or the Kurdistan Region, and how we can benefit from these experiences and extract information from them. Despite having clear law in the parameters of foreign investment in the Kurdistan Region, at the same time it has not achieved the expected ambition to attract foreign investment. The investment was able to help in developing and expanding the economy for the reconstruction of the Kurdistan Region, which has suffered for so long from the battles that took place and led to the destruction of villages and cities. Investing and creating the development environment for the region and economic development in order to raise the standard of living for individuals, leads to a fundamental change in the economic and social structure. The laws of the Kurdistan Region have few gaps and shortcomings about foreign investment. In order to fill these gaps, you can benefit from others laws, for example, to benefit from federal laws